Mantiq dan Logika Bahasa - abid1000; Ar-Rusi, Wilma; Husain Al Farouq, Muhammad; Hafidhoh Azzahro, Nurul (Hamka Ilmu Pendidikan Islam, 2025)
This study aims to analyze the relationship between mantiq (logic) and communication, with a particular focus on the role of language as a medium for expressing rational thought. The findings reveal an intriguing insight: although logic is commonly regarded as the foundation of rational communication, in practice especially in contexts such as advertising, political speeches, religious edicts (fatwas), and Islamic sermons language is often employed in non-transparent ways through ambiguity, euphemism, and rhetorical manipulation. These strategies are primarily designed to influence audiences rather than convey truth in a logically coherent manner. This phenomenon exposes an irony: forms of communication that appear “rational” frequently sacrifice clarity and semantic precision for persuasive or ideological purposes. Theoretically, this research contributes to expanding the understanding of classical mantiq into the pragmatic domain of modern communication, while also critiquing the assumption that rationality is inherently present in logical structures without considering the ethical and rhetorical dimensions of language use.